Social inequality as a collective practice, beyond equal opportunities (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of the article was the configuration of an interpretation about social inequality as part of a capitalist society, which has undergone changes at the time when salaried work was separated from social protections, derived from a state welfare system. This generated a multiplied social inequality, where social assistance has been insufficient to stop the negative consequences of a fragmented vulnerability, anchored in the principle of equal opportunities, adjusted with the acceptance of inequality based on merit.
Keywords: Social inequality; vulnerability; merits; equal opportunities